The baseline for micro- and mesoplastic pollution in open Baltic Sea and Gulf of Riga beach - Dimante-Deimantovica, Inta; Bebrite, Alise; Skudra, Māris; Retike, Inga; Viška, Maija; Bikše, Jānis; Barone, Marta; Prokopovica, Anda; Svipsta, Sanda; Aigars, Juris (Frontiers in Marine Science, 2023)
Microplastic pollution has become widespread, occurring even in areas with low anthropogenic impacts, small human populations, and low tourism intensity. Marine beach sand represents the interface between inland and marine environments and acts like a fingerprint of all the processes happening within the onshore catchment and in the sea, driven by marine hydrodynamic processes. An extensive dataset is required from different coastal ecosystems to understand microplastic pollution. Here, we set the baseline for micro- and mesoplastic pollution distribution in 24 beaches along the Latvian coastline (Northern Europe, Baltic states), filling the existing knowledge gap and contributing to the global understanding of microplastic particles presence, transport, and the processes governing its dynamics. We also highlight citizen science as a fundamental tool to support data collection and raise awareness about microplastic pollution, as samples were collected by up to 250 volunteers during organized campaigns. To improve the understanding of the driving forces responsible for plastic pollution distribution along beaches, we analyzed sand granulometry, sample location, hydrodynamic variables (waves and currents), and tourism/leisure intensity. Our results demonstrate that the semi-closed Gulf of Riga beach environment contains fewer micro- and mesoplastic particles (0.10 particles/kg dry sand) compared to the open Baltic Sea (0.16 particles/kg dry sand). For microplastic size fraction particularly, a separate cluster can be distinguished showing a higher microplastic concentration and greater presence of fibers associated with coarser beach sand in the open Baltic Sea and eastern part of the Gulf of Riga. Recreational activity was not observed to have any statistically significant effect on microplastic distribution. We have concluded that hydrodynamics is an important factor for microplastics distribution and accumulation, but the impacts are of local scale, and results vary significantly among existing studies.